PERBANDINGAN PERPINDAHAN LATERAL GEDUNG BETON BERTULANG DENGAN DAN TANPA DINDING GESER - Dermawan Zebua; Leonardus Setia Budi Wibowo (LPPM Universitas Abdurrab, 2022)
Earthquakes that often occur in Indonesia are tectonic earthquakes. Indonesia is one of the countries in the earthquake area. Thus, the construction of structures built in earthquake-prone areas must meet applicable national standards and the structures can still function and be safe from earthquakes affected by the earthquake. Reinforced concrete shear walls are one of the structural elements that effectively resist earthquake forces. The application of reinforced concrete shear walls can effectively reduce the displacement and shear forces of the structure floor. This study aims to determine the effect of shear wall position on symmetrical high-rise buildings due to earthquake loads. In this research, the building that is analyzed is earthquake by considering two types of structural systems. Namely the frame system and the dual system. The first model is an open frame structure system, and the other three models are a double type structure system. The dual system with shear walls in the core and placed in the center of the building showed a significant reduction of more than 85% of lateral displacement at the top of the structure